1998
DOI: 10.1177/0899764098272004
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Effectiveness of Nonprofit Boards

Abstract: The Board Self-Assessment Questionnaire (BSAQ) was developed to assess board performance in six areas that previous research has shown to characterize highly effective boards. Data from 623 board members in 34 nonprofit organizations were used to examine this instrument's reliability, validity, and sensitivity, including the relationship between board scores and selected indicators of the organization's financial performance. Results indicate that the BSAQ is a sound and useful tool for evaluating board perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 117 publications
(86 citation statements)
references
References 11 publications
1
85
0
Order By: Relevance
“…As in previous research, 29,42,44,45 this analysis has shown the validity of the six BSAQ dimensions. The study improves on previous analyses by doing a factor analysis applied to ordinal data, calculating both factor scores and factor-based scales and developing a composite BSAQ score from the factor scores.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…As in previous research, 29,42,44,45 this analysis has shown the validity of the six BSAQ dimensions. The study improves on previous analyses by doing a factor analysis applied to ordinal data, calculating both factor scores and factor-based scales and developing a composite BSAQ score from the factor scores.…”
Section: Discussionmentioning
confidence: 49%
“…29,42,44,45 Contribution of items in the common factor Each of the dimensions in BSAQ has a number of questions that load onto that dimension; for example, there are 12 questions/items in the contextual domain, but only eight questions/items in the political domain. The factor loadings presented in Table 10 indicate the extent to which each of the items correlate with the underlying factor.…”
Section: National Survey Of Nhs Boardsmentioning
confidence: 99%
See 2 more Smart Citations
“…They made use of the findings from their assessments to identify areas, issues, or practices in which they wanted to strengthen the board' s performance (Jackson and Holland, 1998, report one such approach).…”
Section: Using Feedback From Evaluationsmentioning
confidence: 99%